Industrial Training-Objectives and Students Role - Patankar, P. R. (Journal of Engineering Education Transformations, 1994)
The great majority of passouts from engineering colleges or polytechnics are destined for a productive life of practical action. They are going to do things, design things, make things, organize things, for the most part of their professional career in coopertaion with other people.